Economic cooperation In Turkish culture: Public goods games and lonely elephants - Benjamin Beranek; Alper Duman (Izmir University of Economics, Department of Economics, 2010)
While the public good experiment has been used to analyze cooperation among various groups in Western Europe and North America, it has not been extensively used in other contexts such as Turkey. This project seeks to rectify that and explore how Turkish university students informally self govern. By employing the public good experiment among a cohort of students attending universities in çIzmir, Turkey and Adyaman, Turkey, we hope to quantitatively analyze the factors which lead to altruistic punishment, to antisocial punishment, and ultimately to enhanced cooperation in Turkish society.
Keywords: C9; 330; Cooperation; Free Riding; Altruism; Punishment; Trust; Experimental Economics; Public Good Experiments; Kooperation; Studierende; Öffentliche Güter; Trittbrettfahrerverhalten; Altruismus; Vertrauen; Experimentelle Ökonomik; Türkei